Simulating the Reiner Gamma Swirl: The Long‐Term Effect of Solar Wind Standoff. Issue 5 (11th May 2020) - Deca, J.; Hemingway, D. J.; Divin, A.; Lue, C.; Poppe, A. R.; Garrick‐Bethell, I.; Lembège, B.; Horányi, M.
Abstract: The Reiner Gamma swirl is a prime location to investigate the lunar albedo patterns and their colocation with magnetic anomalies. The precise relationship between impinging plasma and the swirl, and, in particular, how these interactions vary over the course of a lunar day, remains an open issue. Here we use a fully kinetic particle‐in‐cell code, coupled with a magnetic field model based on orbital‐altitude observations, and simulate the interaction with the Reiner Gamma anomaly for all plasma regimes the region is exposed to along a typical orbit, including different solar wind incidence angles and the Moon's crossing through the terrestrial magnetosphere. Consistent with the hypothesis that swirls form as a result of plasma interactions with near‐surface magnetic fields, we show that the energy flux profile produces a pattern similar to Reiner Gamma's alternating bright and darkly colored bands, but only when integrating over the full lunar orbit. We additionally show that including He 2 + as a self‐consistent plasma species improves the match. Plain Language Summary: The Moon is dotted with visually distinctive brightness variations, called "lunar swirls." Measurements have shown that all swirls are colocated with some of the tiny magnetic fields that are present on the surface. One of the most famous regions, in this respect, is the Reiner Gamma swirl. Simulating the plasma environment surrounding Reiner Gamma, using also the observed magnetic fields from two recent spacecraft missions to the Moon, we find that the flux of energy to the surface is consistent with the optical brightness pattern when the proton and helium components of the solar wind are both included. Detailing how certain areas of the lunar surface are shielded better than others from impinging plasma could help us understand better how space weathering processes alter the optical properties of exposed surfaces over time. The morphology of swirls may be telling us about the fine‐scale near‐surface magnetic field structure, thus helping to constrain the origins of the underlying crustal magnetic sources and how they relate to the early thermal and magnetic history of the Moon. In addition, understanding the plasma environment near Reiner Gamma is imperative, as it is one of the prime targets for future low‐orbiting spacecraft or even lunar landers. Key Points: Solar wind standoff can explain the correlation between the Reiner Gamma swirl and the colocated magnetic anomaly The outer bright lobes emerge in the simulated weathering pattern only when integrating over the entire lunar orbit Both the proton and helium energy flux to the surface need to be taken into account to best reproduce the swirl pattern